Penerapan Konseling Kelompok REBT dalam Menangani Disfungsi Emosional Remaja - Nabila Rezky Palenza; Yeni Karneli; Netrawati Netrawati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Adolescents are a group that is vulnerable to emotional dysfunction due to academic, social, and family pressures. Group counseling based on Rational Emotive Behavior Therapy (REBT) is a potential approach to help adolescents manage negative emotions. This study aims to analyze various literature related to the effectiveness of REBT group counseling in dealing with emotional dysfunction in adolescents. Based on literature studies from various journals and books, REBT group counseling has been proven effective in reducing symptoms of anxiety, depression, and irrational behavior in adolescents. The implications of these findings are important for education practitioners and school counselors.